Mental health and ischemic stroke in young adults: A case-crossover study in Iran - Mahdiyeh Khodabandehlou (Journal of Biostatistics and Epidemiology, 2016)
Background & Aim: Stroke in young adults is rare but can be devastating for the affected individuals and their families. Some triggers of stroke may be acute but transient effects on the pathophysiological condition while other factors may be effective overa longer period. Methods & Materials: This study was a case-crossover study on 18 young adults. The study included patients aged 15-49 years who hospitalized for ischemic stroke for the first time from June 2012 to September 2013. In this study, mental health status was considered during the 6-month period so that exposure within 1 month of stroke onset (hazard period) was compared with exposure during five control periods of 1 month preceding the hazard period. Results: Conditional logistic regression showed there was an association between mental health and stroke so that for every 5 unit increase in mental health, odds of stroke will increase about 13-fold.In the other words, much higher scores on mental health, mental health condition weaker. Conclusion: Mental health status is associated with the occurrence of ischemic stroke in young adults so that whatever mental health condition weaker odds of ischemic stroke incidence is high.